Structure‐Activity Relationship Studies of Hydantoin‐Cored Ligands for Smoothened Receptor - Dr. Yang Liu; Dr. Fang Zhou; Kang Ding; Dr. Dongxiang Xue; Zhihao Zhu; Cuixia Li; Fei Li; Dr. Yueming Xu; Prof. Fei Xu; Prof. Zhiping Le; Prof. Suwen Zhao; Prof. Houchao Tao (ChemistryOpen, 2021)
Abstract An underside binding site was recently identified in the transmembrane domain of smoothened receptor (SMO). Herein, we report efforts in the exploration of new insights into the interactions between the ligand and SMO. The hydantoin core in the middle of the parent compound was found to be highly conservative in chirality, ring size, and substituents. On each benzene at two ends, a plethora of variations, particularly halogen substitutions, were introduced and investigated. Analysis of the structure‐activity relationship revealed miscellaneous halogen effects. The ligands with double halogen substituents exhibit remarkably enhanced potency, providing promising candidates that potentially overcome the common drug resistance and useful heavy‐atom labeled chemical tools for co‐crystallization studies of SMO.